Problemy przekazywania indywidualnych gospodarstw rolnych w ramach systemu emerytalnego rolników - Paszkowski, Stanisław (Wydział Prawa i Administracji UAM, 1987)
The article presents the causes of non-conveyance of farms within the Law of October 27, 1977 on old-age pensions for farmers, and the economic characteristics of such farms. The survey, carried out 4 years after the Law of 1977 had come into force, included 3361 farms from the middle, western and northern territories of Poland. Two groups of farms have been distinguished with respect to the causes of non-conveyance: the farms with or without successors. The following features have been analysed: the area, the value of sold production, the age, sex and the social and professional status of farmers. The analysis indicates that 9,1% of private farms are run by farmers in the retirement age. Among them one in four has no successor. One farm in three has not been conveyed due to the farmers' disapproval of the solutions adopted by the Law of 1977, namely the way of conveying a farm and insufficient pensions. One third of all farms have not been conveyed because of the reasons pertaining to the farmer's family and one fourth because of the reasons concerning the farmer. Non-conveyed farms are characterized by low level of sold production and considerable average area; both factors add to the decrease of production capacities of private farming.
Farms run by farmers in the post-productive age and the causes of non - conveyance of such farms within the old-age pensions system